Evaluation of Laser-Assisted Bone-Cutting Techniques Compared to Traditional Methods - K P Noufal; RP Shanoj; Mohammad Assaggaf; R Sunil; Deepika Rayan Pai; Reshma Amin (Journal of Pharmacy and Bioallied Sciences)
Background: Laser-assisted bone cutting has emerged as a promising alternative to traditional methods, such as rotary instruments and saws. The technique is considered minimally invasive, offering potential benefits in precision, reduced trauma, and faster healing. Materials and Methods: A randomized clinical trial was conducted involving 100 patients requiring bone resection for various dental procedures. Participants were divided into two groups: Group A (n = 50) underwent laser-assisted bone cutting using a 2940 nm Er laser, while Group B (n = 50) received traditional bone cutting using rotary instruments. Both groups were evaluated based on operative time, thermal damage to surrounding tissues, postoperative pain, and healing rate over a follow-up period of four weeks. Quantitative assessments included operative time (minutes), thermal impact (measured in tissue temperature increase), and patient pain scores using a visual analog scale (VAS). Results: Group A (laser-assisted) demonstrated an average operative time of 25 ± 4 minutes, compared to Group B’s 20 ± 3 minutes, reflecting a marginally longer procedure for laser use. However, thermal damage was significantly lower in Group A, with a tissue temperature increase of only 3.5°C ± 0.2 compared to 5.2°C ± 0.3 in Group B (P < 0.05). Postoperative pain scores were notably lower in the laser group (VAS score of 2.8 ± 0.5) compared to the traditional method group (VAS score of 4.5 ± 0.6). Furthermore, the healing rate was faster in Group A, with 80% of patients exhibiting optimal healing within two weeks, whereas only 55% in Group B reached a similar status (P < 0.05). Conclusion: Laser-assisted bone-cutting techniques provide a viable alternative to traditional methods, with advantages in reduced thermal damage, decreased postoperative pain, and faster healing, albeit with a slight increase in operative time.